ECOFEMINIST RESISTANCE IN ROBERT STROMBERG’S MALEFICENT 1 (2014): THE STRUGGLES OF WOMEN AND NATURE AGAINTS PATRIARCHAL DOMINATION - Faulia Azizi, Helga; Yulistiyanti, Yulistiyanti (BASIS (Bahasa dan Sastra Inggris), 2025)
This study aims to examine the struggles of Maleficent’s character in Robert Stromberg’s Maleficent (2014) to assert her existence as both a woman and a guardian of nature. It uses Karen J. Warren’s ecofeminist theory, which explains how patriarchal domination connects the oppression of women and the exploitation of nature. The film Maleficent (2014) serves as the primary data source. This study applies a qualitative descriptive method, with data collected through close observation of the film’s narrative, dialogue, and character development. The analysis was conducted using a contextual approach, guided by Klarer’s literary theory and Warren’s ecofeminist framework, particularly focusing on the concepts of the logic of domination, sexism, and naturism. The findings reveal that Maleficent’s resistance through the creation of protective boundaries, leadership of the Moors, and reclamation of her agency mirrors the broader resilience of women and nature under patriarchal systems. The study concludes that the film presents an alternative narrative where healing, protection, and empowerment appear through feminine strength and ecofeminist values.